Comparison of postpartum sonographic findings after uneventful vaginal and cesarean section deliveries - Isil Uzun Cilingir; Cenk Sayin; Havva Sutcu; Ebru Alici; Cihan Inan; Selen Erzincan; Cem Yener; Fusun Varol (Journal of Ultrasonography, 2019)
Objective: To prospectively determine the sonographic findings of the postpartum uterus 24 hours after vaginal delivery and cesarean section. Methods: Women who had uneventful vaginal delivery or cesarean section from July 2015 to May 2018 in a tertiary care hospital were prospectively included. Uterine lengths, endometrium, amout of free fluid, the distance between the uterine fundus-promontorium and uterine fundus-L5 were evaluated 24 hours after delivery. Results: The mean (min–max) endometrial thickness in the vaginal delivery and cesarean section groups were 13.3 (4–25) and 12.4 (4–29) mm, respectively. Fundus-cervix length was significantly higher in the vaginal delivery group compared to the cesarean section group (184.05 ± 16.8 vs 163.6 ± 6.7 mm, p <0.001). The measurements of anterior and anterior-posterior walls of the uterus, anteroposterior uterine length and uterine width were similar in both groups. Promontorium-fundus length was significantly higher in patients who delivered vaginally than those by cesarean section (123.3 ± 13.6 vs 108.7 ± 23.3 mm, p = 0.005). Conclusion: The measurement of L5-fundus distance is a simple and effective technique to evaluate the size of the uterus. Homogenous endometrium up to 30 mm in asymptomatic patients may be a normal finding 24 hours after delivery. The results of this study may be helpful in the decision-making process in cases of early postpartum hemorrhage or hemodynamic instability.